Variations In Talar Articular Facets on Dry Adult Human Left Calcaneus (Bangladesh Journal of Anatomy, 2020)
Context: Calcaneus, also called the “Heel Bone” is the largest and strongest tarsal bone in humans. It acts as the posterior pillar of the longitudinal arches of foot for the transmission of body weight. The calcaneus articulates with the talus bone superiorly by three articular facets, forming a subtalar joint. Morphological variations of superior articular facets of calcaneus may predispose people to joint instability, ligamentous laxity and development of arthritic changes in the subtalar joint. Knowledge of such variations is essential for treatment and diagnostic procedures in orthopaedic surgeries. The aim of this study is to find out the variations in types of talar articular facets of calcaneus. Materials and Methods: The present study was an observational study conducted on the department of Anatomy, Dhaka Medical College, Dhaka from January 2018 to December 2018. The study material consists of two hundred (200) calcaneus of unknown sex. The study samples were divided into male and female groups using ‘discrimination function analysis technique’ and the variations in talar articular facets on dry adult human left calcaneus were identified by simple observational method. Results: In the male, Pattern I was found in 73%, Pattern II was found in 24% and Pattern III was found in 3% cases. In the female, Pattern I was found in 64%, Pattern II was found in 34% and Pattern III was found in 2% cases. Conclusion: The findings of the present study revealed that Pattern I was common.Bangladesh Journal of Anatomy January 2020, Vol. 18, No. 1, pp. 17-20